Pengaruh Effective Tax Rate, Sales Growth dan Aset Tidak Berwujud terhadap Transfer Pricing - Miftahul Ilma; Indawati Indawati (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to prove the influence of Effective Tax Rate, Sales Growth and Intangible Assets on Transfer Pricing in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange in 2019-2023. This type of research is quantitative and uses secondary data. The data analysis method used is panel data regression test using Microsoft Excel and Eviews 12. The population used is all Consumer Non-Cyclicals sectors listed on the Indonesia Stock Exchange in the period 2019-2023. This study collected data using a purposive sampling method that combines 125 populations into 21 research samples. The results of the study state that Effective Tax Rate, Sales Growth and Intangible Assets have a joint effect on Transfer Pricing in Consumer Non-Cyclicals sector companies in the period 2019 to 2023. While partially Effective Tax Rate has no effect on Transfer Pricing, Sales Growth has no effect on Transfer Pricing and Intangible Assets have an effect on Transfer Pricing.